Metabolomics analysis of the anti-inflammatory activity of Scurrula ferruginea (Jack) danser parasitizing on three different host plants, and insights into possible mechanism - Hong, Xia (2020)
Scurrula ferruginea (Jack) Danser of Loranthaceae family is a hemi-parasitic shrub that grows on a dicotyledonous tree. Despite its traditional use for a long time in some disorders, there is very limited research on its bioactivities and phytochemistry, as well as, there is also no research concerning the influence of the host plants on the chemistry and bioactivity of S. ferruginea. The main purpose of this study was to evaluate the anti-inflammatory activity of S. ferruginea and the mechanism of action, as well as determine the relationship between the metabolites of S. ferruginea with its anti-inflammatory potency. The anti-inflammatory activity was assessed via inhibition of nitric oxide (NO) production in lipopolysaccharide (LPS) and interferon-γ (IFN-γ) induced RAW 264.7 macrophage cells. The air dried and freeze dried S. ferruginea parasitizing on Vitex negundo were investigated firstly. The results showed freeze drying was the most appropriate drying method for the anti-inflammatory activity. Subsequently, the anti-inflammatory ability was evaluated on the freeze dried leaves and stems of S. ferruginea parasitizing on three different hosts. The results showed that S. ferruginea stems parasitizing on Tecoma stans and Vitex negundo exhibited higher anti-inflammatory activity compared to the corresponding samples of harvesting from Micromelum minutum, and to the corresponding S. ferruginea leaf samples. Their IC50 values of the two S. ferruginea stems were 114.47 ± 2.96 and 118.87 ± 2.31μg/mL, respectively. Then, the anti-inflammatory mechanism was deciphered through messenger Ribonucleic acid (mRNA) and protein expression of the inflammatory cytokines, including inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), interleukin (IL), and tumor necrosis factor (TNF). The techniques of reverse transcriptase and real time quantitative polymerase chain reactions (RT-PCR and qPCR) were employed. The stem of S. ferruginea hosted on Tecoma stans exerts anti-inflammatory capability attributed to the suppression of iNOS and IL-1β mRNA expression, as well as the protein production inhibition of IL1β, IL-6, IL-10, and TNF-α besides NO secretion inhibition. Afterwards, the metabolite variation was examined using proton nuclear magnetic resonance (1H NMR) and liquid chromatography mass spectrometry (LC-MS) combined with multivariate data analysis (MVDA). The metabolomics approach was employed in evaluating the metabolite variation and its relationship with the anti-inflammatory activity. Principal component analysis (PCA) indicated clear discriminations among the different plant parts and host plants based on the identified metabolites. Quercitrin, 4”-O-acetylquercitrin, catechin, gallic acid and chlorogenic acid, as well as alanine, valine, leucine, isoleucine, malic acid, succinic acid, citric acid, and acetic acid were found higher in the leaf extracts. While threonine, histidine, fumaric acid and choline were found present mainly in the stems. The stem of S. ferruginea-T. stans also possessed higher quercitrin, 4”-O-acetylquercitrin, catechin, valine, leucine, isoleucine, fumaric acid, gallic acid, chlorogenic acid, and sucrose than the stems of S. ferruginea-V. negundo and S. ferruginea-M. minutum. A correlation was observed from partial least square regression (PLS) model that the anti-inflammatory bioactivity might be associated with the presence of choline, isoleucine, catechin, leucine, and chlorogenic acid, as well as some unidentified metabolites such as ions mass m/z at 369.1157, 401.0851, 431.1327, and 473.1794. Lastly, the bioactive-activity guided fractionation by liquid-liquid extraction on freeze-dried stem of S. ferruginea hosted on T. stans was carried out. The results showed that ethyl acetate fraction displayed the highest NO inhibition with 84.8 ± 1.45% at 200 μg/mL. Chloroform fraction displayed higher activity than n-butanol and ethyl acetate fractions at 50 μg/mL, but CHCl3 fraction showed more cytotoxicity towards the RAW 264.7 cells. The catechin was elucidated in the ethyl acetate fraction. This is the first report on the antiinflammatory activity of S. ferruginea parasitizing on different host plants, as well as the extensive study concerning its plant metabolites and their correlations with antiinflammatory property using metabolomics. The results of this study lay the foundation for in-depth study of S. ferruginea, and further understanding on the effect of host plants on the bioactivity of the hemiparasitic plant.